Sports performance: A reflection on the start-up and the development of Brazilian soccer players - Verardi, Carlos Eduardo Lopes [UNESP]; Freitas, Vinicius de Lima; Maffei, Willer Soares [UNESP]; Hirota, Vinicius Barroso; de Marco, Ademir (My University, 2016)
This study aimed to analyze the perception of children and adolescents on the emotional states with emphasis on the motivational aspect as well as its related in the involvement in soccer with a team that pursues the sport as performance. The sample consisted of male children and adolescents (n = 30), age range was limited to the minimum of 8 years and a maximum of 14 years with a mean age of 12.03 (±1.94) years. A questionnaire containing closed questions directed to children and adolescents was used. Findings showed that children and teenagers who plays soccer with the goal toward high performance report the existence of a reinforcing emotion when they receive “praise from the coach” a factor that generates pleasure and satisfaction.
Keywords: Motivation; Soccer; Sports initiation